Biomarker Analysis Revealed Distinct Profiles of Innate and Adaptive Immunity in Infants with Ocular Lesions of Congenital Toxoplasmosis. (18th September 2014) - Machado, Anderson Silva; Carneiro, Ana Carolina Aguiar Vasconcelos; Béla, Samantha Ribeiro; Andrade, Gláucia Manzan Queiroz; Vasconcelos-Santos, Daniel Vitor; Januário, José Nélio; Coelho-dos-Reis, Jordana G.; Ferro, Eloisa Amália Vieira; Teixeira-Carvalho, Andréa; Vitor, Ricardo Wagner Almeida; Martins-Filho, Olindo Assis; —UFMG-CTBG, UFMG Congenital Toxoplasmosis Brazilian Group
Abstract : Toxoplasma gondii is the main infectious cause of human posterior retinochoroiditis, the most frequent clinical manifestation of congenital toxoplasmosis. This investigation was performed after neonatal screening to identify biomarkers of immunity associated with immunopathological features of the disease by flow cytometry. The study included infected infants without NRL and with retinochoroidal lesions (ARL, ACRL, and CRL) as well as noninfected individuals (NI). Our data demonstrated that leukocytosis, with increased monocytes and lymphocytes, was a relevant hematological biomarker of ARL. Immunophenotypic analysis also revealed expansion of CD14 + CD16 + HLA-DR high monocytes and CD 56 dim cytotoxic NK-cells in ARL. Moreover, augmented TCR γ δ + and CD8 + T-cell counts were apparently good biomarkers of morbidity. Biomarker network analysis revealed that complex and intricated networks underscored the negative correlation of monocytes with NK- and B-cells in NRL. The remarkable lack of connections involving B-cells and a relevant shift of NK-cell connections from B-cells toward T-cells observed in ARL were outstanding. A tightly connected biomarker network was observed in CRL, with relevant connections of NK- and CD8 + T-cells with a broad range of cell subsets. Our findings add novel elements to the current knowledge on the innate and adaptive immune responses in congenital toxoplasmosis.